Wavelet analysis of the first pulse of initial breakdown process in lightning discharges - Esa, M. R. M. (2013)
Wavelet transformation is used in order to seek for differences in the initial break- down process between negative cloud-to-ground flash (CG−), positive CG (CG+), cloud flash (IC), and isolated breakdown (IB) processes. 72 waveforms were selected from 885 waveforms recorded between May and August 2010 at the premise of Uppsala University, Uppsala, Sweden. The analysis was conducted only on the first electric field pulse for each lightning process and the output from the wavelet transformation is plotted as normalized power spectrum. The first pulses in CG− are found to radiate intensely in average frequency between 186 and 1637kHz. The energy radiated by the first pulses of CG+ mainly concentrated in the average frequency between 57 and 599kHz. As for the IC, the first pulses found to be spread out in the average frequency between 461 and 3570 kHz and for IB, the energy spread out between 44 and 279 kHz. The CG+ and IB flashes tend to radiate at lower frequency region within smaller range compared to CG− and IC. IB has the smallest frequency range around 235 kHz while the frequency range of IC and CG− are more than 10 times and 6 times larger than IB, respectively. Furthermore, IC and CG− have comparable initial-to-overshoot peak ratio with 1.7 and 1.6, respectively, which higher than CG+ and IB at least with a factor of 1.4. It can be speculated that the initial breakdown processes of IC and CG− flashes are most likely initiated from the same discharge process in the thundercloud and differ from the discharge process of CG+ and IB.